2001
DOI: 10.1186/1471-2458-1-17
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis B and C markers in high-risk hospitalised patients in Crete: a five-year observational study

Abstract: Background: So far the prevalence of viral hepatitis infection in hospitalized patients has not been extensively studied. Therefore we conducted the present five-year observational study to evaluate the prevalence of HBV and HCV infection in high-risk hospitalized patients of Crete, the largest Greek island, Due to the homogeneous population, epidemiological studies can be accurately done.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 15 publications
(25 reference statements)
2
10
1
6
Order By: Relevance
“…In the present study, the detected total seroprevalence of HCV was slightly lower than the lower limit of the recorded national range. This rate also was lower than that reported elsewhere in Egypt in Ismailia, (14.9%) (11) but higher than that reported in Greece (4.7%) (13), in Turkey (0.5%) (12) and in Pakistan (1.6%) (14). This could confirm the endemicity of HCV in Egypt.…”
Section: Discussioncontrasting
confidence: 55%
“…In the present study, the detected total seroprevalence of HCV was slightly lower than the lower limit of the recorded national range. This rate also was lower than that reported elsewhere in Egypt in Ismailia, (14.9%) (11) but higher than that reported in Greece (4.7%) (13), in Turkey (0.5%) (12) and in Pakistan (1.6%) (14). This could confirm the endemicity of HCV in Egypt.…”
Section: Discussioncontrasting
confidence: 55%
“…In Southern Europe (i.e. Spain, Italy, Greece, Southern France), the overall prevalence ranges between 2.5% and 3.5% [2,8,[11][12][13][14][15][16]. In these countries, an initial epidemic (occurring >50 years ago) of iatrogenic nature led to a high infection prevalence in older people, followed, some 30 years later, by a still-ongoing IDUrelated epidemic which spread the infection among younger people [17].…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 1 shows the current estimated prevalence of HCV infection in Europe [2,6,[9][10][11][14][15][16]21,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…The virus is transmitted either during the period of breastfeeding or at primary school entry at 6-7 years of age. In study of Koulentaki et al, 2001 reported that HBsAg prevalence was found in the males were 5.4% and female were 3.09% respectively. In our study among the male samples 5.12% were HBsAg positive and female samples 3.64% were HBsAg positive, which was similar to previous study.…”
Section: Resultsmentioning
confidence: 99%